If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2.1 = 6.5 Reorder the terms: 2.1 + 2x = 6.5 Solving 2.1 + 2x = 6.5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.1' to each side of the equation. 2.1 + -2.1 + 2x = 6.5 + -2.1 Combine like terms: 2.1 + -2.1 = 0.0 0.0 + 2x = 6.5 + -2.1 2x = 6.5 + -2.1 Combine like terms: 6.5 + -2.1 = 4.4 2x = 4.4 Divide each side by '2'. x = 2.2 Simplifying x = 2.2
| 2(-14-7)=3*-14 | | p^2=-4p-3 | | -20x+-84+5x+21=6 | | 4(x+2)+7=35+2(x+4) | | .4(x-20)=-6 | | -1.4=4.6-2y | | 6(100-8)= | | -38+8Y+3=2(5Y-4)-9 | | 12x-3(5+4x)=-15 | | 7x/2=49 | | x^2+x=500000000000000000 | | 2/x=x-4/16 | | 12(5+2y)=-4y-(6-9y) | | y^2-14y=26 | | x^2+x=500000000000000 | | 9(3)+9(5)= | | 2(x-7)=-3x | | x^2+x=y | | -2+14=14x-4-13x | | ln(5x+2)-ln*x=ln*6 | | -3x^2+44x+0=0 | | i(2x-4y)=4x+2-iy | | 45x^2=0 | | x^2+x=500000000000 | | 3(x-4)=108/12 | | 1-x=6x-48 | | 9x+3=-5+6x+17 | | y^2-2y+17=0 | | 9(w-8)=-7w+8 | | 3x-(-5-4x)=-9 | | -4(-5x+21)+y=6 | | -5x-9=4x+9 |